REALITIES OF THE TIME: IDIOPATHIC THROMBOCYTOPENIC PURPLE AND PREGNANCY - Askarova Fotima Kudratovna (Scholar Express Journals, 2022)
The article presents the data of examination of pregnant patients with idiopathic thrombocytopenic purpura, studied the data of the course of pregnancy and childbirth. As a result of the study, a tactic of rational management and treatment of patients was developed depending on the stage and form of the pathological process, which helps to reduce the risk of exacerbations and complications of the mother's disease, the successful course and completion of the gestational process and antenatal protection of the fetus.
Keywords: gestation; pregnancy; idiopathic thrombocytopenic purpura (ITP)